Eulejeunea crenulata Schiffn., a new synonym of Lejeunea umbilicata (Lejeuneaceae, Marchantiophyta) - Wei, Yu-Mei; Ho, Boon-Chuan; Tang, Qi-Ming (Phytotaxa, 2019)
Stephani (1915) proposed the transfer of Eulejeunea crenulata Schiffner (1890: 33) to Lejeunea Libert (1820: 373). However, as the combination already existed and thus not available for use, Lejeunea crenulata (Schiffn.) Stephani (1915: 784) is a later homonym of Lejeunea crenulata Mitten (1871: 415). Nonetheless, Eulejeunea crenulata remains a validly published name (Söderström et al. 2015). According to the recent compilation of species binomials in Lejeuneaceae published between 1884 and 1893 (Söderström et al. 2015), Eulejeunea crenulata is listed as a heterotypic synonym of Lejeunea patersonii (Stephani 1896: 92) Stephani (1915: 784) following Hürlimann (1993). However, this is an error as Hürlimann (1993) cited Lejeunea crenulata Mitten as a synonym of Lejeunea patersonii, following Grolle (1980), and not Eulejeunea crenulata Schiffn. (Lejeunea crenulata (Schiffn.) Steph.). This has prompted us to revisit the true identity of Eulejeunea crenulata.